High Prevalence of Early Parkinson's Disease in Patients With Subtle Parkinsonian Signs - Sasaki, Shoichi (Frontiers in Neurology, 2021)
Background: Little is known about how frequently patients with a Unified Parkinson Disease Rating Scale part III (UPDRS-III) score of 3 or 4, including postural and action tremor could be classified into early Parkinson’s disease (PD). Objective: To examine the prevalence of early PD in patients with subtle parkinsonian signs (rest tremor, postural tremor, and rigidity) without bradykinesia, having a UPDRS-III score of 3 or 4. Methods: Parkinsonism was assessed using UPDRS-III based on both the United Kingdom PD Society Brain Bank criteria and the Movement Disorder Society PD criteria. Ninety patients with a UPDRS-III score of 3 or 4, including postural tremor were evaluated by 123I-FP-CIT SPECT (DaTscan), brain MRI, the Mini-Mental State Examination, and smell test. Some patients were additionally examined by 123I-metaiodobenzylguanidine myocardial scintigraphy or 123I-N-isopropyl-p-iodoamphetamine SPECT. Results: 75 (mean age [standard deviation]: 76.9 [8.1]) out of 90 patients (83.3%) showed abnormal findings on DaTscan imaging: 57 out of 75 (76.0%) showed a reduced specific binding ratio (SBR) accompanied by an egg shape pattern (n=37, 49.3%) or a mixed type pattern (n=14, 18.7%), both reduced SBR and increased asymmetry i¬ndex (AI) with a normal shape (n=4, 5.3%), reduced SBR only (n=2, 2.7%); 18 (24.0%) showed an egg shape pattern or a mixed type pattern without reduced SBR. In other words, 69 out of 75 patients (92.0%) showed either an egg shape or a mixed type pattern with or without reduced SBR. All patients were free of dementia, and their olfactory function was significantly impaired compared with controls (n=141) on the odor-stick identification test for Japanese (p<0.0001). Conclusions: The prevalence of patients with subtle parkinsonian signs having a UPDRS-III score of 3 or 4, including postural tremor is unexpectedly high in daily clinical practice, and most of these patients could be categorized into mild early-stage PD.